Clinical parameters and adrenocortical activity to assess stress responses of alpacas using different methods of restraint either alone or with shearing. (10th June 2017) - Wittek, T.; Salaberger, T.; Palme, R.; Becker, S.; Hajek, F.; Lambacher, B.; Waiblinger, S.
Abstract : Shearing of alpacas is stressful and is undertaken by restraint in the standing position, cast on the floor or on a tilt table. The objectives of the study were to evaluate and compare the stress responses between different methods. The study consisted of two parts. In part one, 15 animals were restrained applying all three methods but without shearing. In part two, 45 animals in three groups of 15 were shorn using one of the three procedures. Body temperature, heart rate, respiratory rate, salivary cortisol and faecal cortisol metabolites (FCM) were measured. Part 1: restraint in a standing position was less stressful than other procedures. Part 2: the classic clinical parameters changed significantly over time but without significant differences between the methods. The number of injuries did not differ. Saliva cortisol and FCM concentrations varied in wide ranges between animals. An increase in FCM concentrations occurred in all groups but saliva cortisol concentration increased only after shearing on the ground. The recommendations of the study are to shear calm alpacas in the standing position but animals showing severe defence reactions should be shorn either cast on the ground or on a table to decrease the risk of injuries.